The Impact of Polyunsaturated Fatty Acid Supplementation on Inflammatory Markers in Preterm Infants – A Literature Review - Bielecka, Larysa (Journal of Education, Health and Sport, 2025)
Introduction Inflammation in fetuses and newborns, particularly in the population of preterm infants, is associated with increased mortality and adverse health outcomes. It has been shown that the placental transfer of polyunsaturated fatty acids (PUFAs) is limited in very preterm infants. Studies have demonstrated that low levels of PUFAs correlate with the severity of inflammation in infants’ bodies. They are also associated with an increased incidence of diseases, including bronchopulmonary dysplasia and retinopathy of prematurity. One of the beneficial effects of PUFA supplementation is its inhibitory action on inflammatory processes in the body. Aim of the study Supplements containing fatty acids are among the most popular complementary health interventions introduced in children. Considering this potential benefit, we would like to present research studies that describe the relationship between the supplementation of polyunsaturated fatty acids and the levels of inflammatory markers in preterm infants. Materials and Methods A review of randomized clinical trials (RCTs) published in 2020-2024 regarding the relationship between the supplementation of polyunsaturated fatty acids and the levels of inflammatory markers in preterm infants. Three studies meeting specific selection criteria were identified. Results All the studies discussed in our work demonstrate that supplementation with polyunsaturated fatty acids in preterm infants reduces the levels of inflammatory markers. Research consistently shows that PUFA supplementation lowers IL-6 levels, a cytokine considered a risk factor for sepsis in preterm infants. Conclusion Supplementation with polyunsaturated fatty acids holds potential for modulating inflammatory processes in preterm infants, with efficacy likely influenced by factors such as the specific type of fatty acid used, timing and form of administration, and individual variations in response.